Analysis of The Effectiveness of Household Scale Smart Window Panel as a New Renewable Energy Source Using PVsyst Software - M Aldi Nugroho; Salsabila Aminatun Muthmainnah; M. Akbar Miftahuzaman; Yohanes Maruli Arga Septianus; Muhammad Irsyad Ivana Akmal; Muhammad Sholeh; Vincentius Glorio Fransduard Gospely Goldant; Cahyaning Hanum Pertiwi (IPTEK The Journal of Engineering, 2023)
Increasing electrical energy consumption causes problems because it produces greenhouse gas emissions. The problem is that the fuel used so far is not renewable. Carbon emissions can trigger global warming. Global warming causes the temperature on earth to increase, causing icebergs in the polar regions to melt and sea levels to rise. Efforts can be made to minimize this problem by transitioning to alternative energy, such as solar panels. Using solar panels as an energy source has an excellent opportunity to be implemented because Indonesia gets sunlight throughout the year. However, solar panels have drawbacks, such as surfaces that are difficult to clean, depending on location and weather conditions, and their installation requires a large area. Therefore, this research was conducted by designing smart window panels that are easy to apply on a household scale so that their effectiveness is known when implemented. The method used in this study is a simulation method using the PVsyst software. The simulation was carried out with a variable angle of installation of the smart window panel, 0°,30°,45°,60°, and 90°. The results showed that the best results were obtained from modules with an installation angle of 90° because the EfrGrid value was 19168 Kw/year and E_Solar was 104.28 Kw/year. Increasing the number of modules used can be done by using suitable inverters so that optimizing the use of smart window panels on the household scale can be done to reduce carbon emissions and achieve energy security in Indonesia.